Apoptosis of resident and inflammatory macrophages before and during the inflammatory response of the virgin bovine mammary gland - Sládek, Zbyšek; Ryšánek, Dušan (Acta veterinaria Scandinavica, 2010)
BACKGROUND: Macrophages may play a prominent role in defense of the bovine mammary gland, and their functionality is necessary for successful eradication of bacterial pathogens. In contrast to necrosis, however, apoptosis has not yet been studied in macrophages from bovine mammary glands. Therefore, the aim of this study was to confirm the occurrence of apoptosis in macrophages from resting heifer mammary glands and during the inflammatory response. METHODS: Inflammatory response was induced by phosphate buffered saline (PBS) and by lipopolysaccharide (LPS). Resident macrophages (RESMAC) were obtained before and inflammatory macrophages (INFMAC) 24, 48, 72 and 168 hours after inducing inflammatory response in mammary glands of unbred heifers. Cell samples were analyzed for differential counts, apoptosis and necrosis using flow cytometry. RESULTS: Populations of RESMAC and INFMAC contained monocyte-like cells and vacuolized cells. Apoptosis was detected differentially in both morphologically different types of RESMAC and INFMAC and also during initiation and resolution of the inflammatory response. In the RESMAC population, approximately one-tenth of monocyte-like cells and one-third of vacuolized cells were apoptotic. In the INFMAC population obtained 24 h after PBS treatment, approximately one-tenth of monocyte-like cells and almost one-quarter of vacuolized cells were apoptotic. At the same time following LPS, however, we observed a significantly lower percentage of apoptotic cells in the population of monocyte-like INFMAC and vacuolized INFMAC. Moreover, a higher percentage of apoptotic cells in INFMAC was detected during all time points after PBS in contrast to LPS. Comparing RESMAC and INFMAC, we observed that vacuolized cells from populations of RESMAC and INFMAC underwent apoptosis more intensively than did monocyte-like cells. CONCLUSIONS: We conclude that apoptosis of virgin mammary gland macrophages is involved in regulating their lifespan, and it is involved in the resolution process of the inflammatory response.
Keywords: Cattle; Animals; skot; apoptóza; zánět; Female; lipopolysacharidy; makrofágy; Apoptosis; ženské pohlaví; lipopolysacharidové receptory; Macrophages; Lipopolysaccharides; kultivované buňky; Mammary Glands, Animal; Lipopolysaccharide Receptors; Inflammation; mléčné žlázy zvířat; regulace genové exprese; Cells, Cultured; Cell Survival; Gene Expression Regulation; zvířata; viabilita buněk